Innovations and advancements in concrete-encased steel shear walls: A comprehensive review - Nima Gharaei-Moghaddam; Mohammad Meghdadian; Mansour Ghalehnovi (Results in Engineering, 2023)
Composite shear walls have emerged as an innovative and efficient solution for resisting lateral loads in high-rise buildings. With the inclusion of these types of shear walls in various design codes and standards, there has been an increasing number of studies aimed at understanding the behavior and performance of these systems. This state-of-the-art review provides a comprehensive analysis of the existing literature on concrete-encased steel plate shear walls, categorizing the studies based on structural configurations, and types of study (experimental, numerical, analytical). Further subcategorization has been performed based on special topics. The review summarizes the key findings, the main adopted assumptions, and the utilized methodologies of each study and provides brief yet critical discussions of the reviewed literature. In addition, comprehensive tables and illustrative figures are presented to summarize the current state of the art. Despite the significant amount of research conducted in this area, there are still several design and performance issues that require further attention, and these are discussed in this study as well. This review serves as a valuable resource for researchers and designers interested in the development and application of CESWs, and highlights areas for future research to improve the performance and design of these systems.